REAKSI PASAR ATAS KINERJA MANAJEMEN MELALUI PUBLIKASI LABA ATAU RUGI PERUSAHAAN (STUDI PADA PERUSAHAAN DENGAN KAPITALISASI PASAR TERBESAR PERIODE JANUARI 2016 YANG TERDAFTAR DI BEI) - CIKITHA ERWONO, ZAFARAYANA (Jurnal Akuntansi AKUNESA, 2016)
Abstract This study aims to examine whether there is any difference in the market reaction is seen through the abnormal return of the companies that publish increased earnings and companies that publish decreased earnings. The study used secondary data obtained from the official website of Indonesia Stock Exchange (www.idx.co.id). The difference is due to the different framing of investors in responsing the different conditions of each company. Data that have been processed using the Mann Whitney U Test (two independent t-test) which produces a significance level of 0.01 (less than the level of significance was set 0.05). So the hypothesis proposed in the study is accepted. Keywords: earnings, investor, market respon